2018
DOI: 10.1111/petr.13151
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric renal transplantation: A retrospective single‐center study on epidemiology and morbidity due to EBV

Abstract: Pediatric R-Tx patients are at high risk of developing EBV primary infection. Although high DNA replication is a risk factor for PTLD, some patients develop PTLD with low viral load. In this retrospective single-center study including all pediatric patients having received R-Tx (2003-2012 period), we aimed to identify risk factors for uncontrolled reactions to EBV (defined as the presence of a viral load >10 000 copies/mL or PTLD). A Cox proportional hazard model was performed. A total of 117 patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…The median CHL duration of 2 years is similar to the results of other studies, but the follow-up time of almost 8 years is longer than other comparable studies [18,27,33]. In a previous multicenter study, 2% of PTLD was reported following renal transplantation [34]. In our study of 58 children, there were no cases of PTLD, which also might be due to the limited study size.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The median CHL duration of 2 years is similar to the results of other studies, but the follow-up time of almost 8 years is longer than other comparable studies [18,27,33]. In a previous multicenter study, 2% of PTLD was reported following renal transplantation [34]. In our study of 58 children, there were no cases of PTLD, which also might be due to the limited study size.…”
Section: Discussionsupporting
confidence: 88%
“…The median time to onset of CHL in our cohort was 69 days post-transplant which is shorter than the 104 days in a previous study [32]. The median CHL duration of 2 years is similar to the results of other studies, but the follow-up time of almost 8 years is longer than other comparable studies [18,27,33]. In a previous multicenter study, 2% of PTLD was reported following renal transplantation [34].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The immunosuppressive treatment impairs the individual cellular immune response resulting in an elevated incidence of severe viral complications, notably after pediatric transplantation. Post-transplant primary infections or reactivations, especially by cytomegalovirus (CMV), BK polyomavirus (BKPyV), or Epstein-Barr virus (EBV) are associated with increased morbidity, mortality, and graft failure, for example from CMV disease [ 7 , 8 ], BKPyV-associated nephropathy [ 9 , 10 ], and EBV-associated post-transplant lymphoproliferative disease [ 11 ]. The outcome of post-transplant viral infections is individually different, but prognostic markers are missing.…”
Section: Introductionmentioning
confidence: 99%
“…After pediatric kidney transplantation, the immunosuppressive treatment disturbs the individual balance between virus replication and cellular immune response resulting in an elevated incidence of severe viral complications. Post-transplant primary infections or reactivations, especially by cytomegalovirus (CMV), BK polyomavirus (BKPyV) or Epstein-Barr virus (EBV), and less frequent by adenovirus (ADV), are associated with increased morbidity, mortality, and graft failure, for example, CMV disease [1], BKPyV-associated nephropathy (BKPyVAN) [2], and EBV-associated post-transplant lymphoproliferative disease (PTLD) [3]. The outcome of post-transplant viral infections is individually different, but prognostic markers are missing.…”
Section: Introductionmentioning
confidence: 99%